Cannabidiol as a Potential New Type of an Antipsychotic. A Critical Review of the Evidence - Rohleder, Cathrin; Müller, Juliane K.; Lange, Bettina; Leweke, F. M. (Frontiers in Pharmacology, 2016)
There is urgent need for the development of mechanistically different and less side-effect prone antipsychotic compounds. The endocannabinoid system has been suggested to represent a potential new target in this indication. While the chronic use of cannabis itself has been considered a risk factor contributing to the development of schizophrenia, triggered by the phytocannabinoid delta-9-tetrahydrocannabinol (Δ9 THC), cannabidiol, the second most important phytocannabinoid, appears to have no psychotomimetic potential. Although results from animal studies are inconsistent to a certain extent and seem to depend on behavioral paradigms, treatment duration and experimental conditions applied, cannabidiol has shown antipsychotic properties in rodents and rhesus monkeys. After some individual treatment attempts, the first randomized, double-blind controlled clinical trial had been conducted and demonstrated that cannabidiol exerts antipsychotic properties in acute schizophrenia comparable to the antipsychotic drug amisulpride accompanied by a superior, placebo-like side effect profile. As the clinical improvement by cannabidiol was significantly associated with elevated anandamide levels, it appears likely that its antipsychotic action is based on mechanisms associated with increased anandamide concentrations. However, a plethora of mechanisms of action has been suggested, but their potential relevance for the antipsychotic effects of cannabidiol needs still to be investigated. The clarification of these mechanisms as well as the establishment of cannabidiol’s antipsychotic efficacy and its hopefully benign side-effect profile remains the subject of a number of previously started clinical trials.